2017
DOI: 10.1093/mnras/stx1079
|View full text |Cite
|
Sign up to set email alerts
|

Lens modelling Abell 370: crowning the final frontier field with MUSE

Abstract: We present a strong lensing analysis on the massive cluster Abell 370 (A370; z = 0.375), using a combination of deep multi-band Hubble Space Telescope (HST) imaging and Multi-Unit Spectroscopic Explorer (MUSE) spectroscopy. From only two hours of MUSE data, we are able to measure 120 redshifts in the Southern BCG area, including several multiply-imaged lens systems. In total, we increase the number of multiply-imaged systems with a secure redshift from 4 to 15, nine of which are newly discovered. Of these, eig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 60 publications
7
119
2
Order By: Relevance
“…Using numerical simulations, Torri et al (2004) have shown that following the evolution of a cluster in cosmic time, the cross-section of radial arc formation can be boosted by a factor of 10 in the presence of asymmetries in the cluster core (see their Figures 5 and 11). This is in agreement with recent studies of FF clusters based on deep MUSE spectroscopy, e.g., MACS 0416 , Abell 2744 (Mahler et al 2017), MACS 1149 (Grillo et al 2016;Treu et al 2016), and Abell 370 (Lagattuta et al 2017). Biviano et al (2013) and Sereno et al (2017) have shown that MACS 1206 is a fairly relaxed cluster; however, the remarkably asymmetric shape of its ICL (Presotto et al 2014) and the distribution of the galaxy members (see Fig.…”
Section: Optimizing the Strong Lensing Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…Using numerical simulations, Torri et al (2004) have shown that following the evolution of a cluster in cosmic time, the cross-section of radial arc formation can be boosted by a factor of 10 in the presence of asymmetries in the cluster core (see their Figures 5 and 11). This is in agreement with recent studies of FF clusters based on deep MUSE spectroscopy, e.g., MACS 0416 , Abell 2744 (Mahler et al 2017), MACS 1149 (Grillo et al 2016;Treu et al 2016), and Abell 370 (Lagattuta et al 2017). Biviano et al (2013) and Sereno et al (2017) have shown that MACS 1206 is a fairly relaxed cluster; however, the remarkably asymmetric shape of its ICL (Presotto et al 2014) and the distribution of the galaxy members (see Fig.…”
Section: Optimizing the Strong Lensing Modelsupporting
confidence: 91%
“…This provides a relatively large number of constraints; however, their identification and distances were based largely on CLASH photometric redshifts, since only three multiply lensed sources had a spectroscopic redshifts from CLASH-VLT at that time. As discussed in our previous strong lensing analysis of the Frontier Field clusters, which take advantage of large sets of spectroscopically confirmed multiple images (Caminha et al 2016a;Grillo et al 2016;Lagattuta et al 2017;Caminha et al 2017;Mahler et al 2017), the use of multiple image systems identified on the basis of their photometric properties is prone to intrinsic systematics in the reconstruction of the internal structure of the mass distribution and in magnification measurements. Nonetheless, the use of a large number of photometric multiple images is often enough to recover the circularized mass density profiles.…”
Section: Comparison With Previous Strong Lensing Analysesmentioning
confidence: 99%
“…Caminha et al (2017) reported the Note. a Corrected for magnification using the lens model of Lagattuta et al (2017).…”
Section: Uv Continuum and Lyα Luminositymentioning
confidence: 99%
“…Our best chance at studying this population in detail with current technology is to identify faint LAEs magnified by the strong-lensing effect of a galaxy cluster (e.g., Ellis et al 2001;Santos et al 2004;Richard et al 2011 Karman et al 2017;Lagattuta et al 2017;Mahler et al 2017). Two of these clusters, Abell 370 and MACS J1149.5+2223, are also being observed by the SHARDS Frontier Fields survey (SHARDS-FF; PI: Pérez-González), an imaging survey with the Gran Telescopio Canarias (GTC) that covers the 500-950 nm spectral range with 25 medium-band filters (R∼50) down to m AB ∼27.…”
Section: Introductionmentioning
confidence: 99%
“…A portion is shown here for guidance regarding its form and content. Galaxies in the field Abell 370 References are as follows: 1 =Lagattuta et al (2017). 2 = GLASS (spectroscopy).…”
mentioning
confidence: 99%